A novel adaptive control algorithm for the rejection of harmonics in a standard vibrator. (February 2022) - Li, Chao; Mao, Chentao; Chen, Zhangwei
Because of the nonlinear factors in the standard vibrators, the output waveform of the vibrators is usually distorted, especially in the low-frequency band. Traditionally, the harmonic distortion is suppressed by improved design of the vibrator and feedback control. However, these approaches can just suppress the harmonics to some extent. There are still residual harmonic components which cannot be eliminated. In this article, an adaptive control algorithm is proposed to eliminate the harmonics of the vibration calibration system by injecting harmonic components into the control input signal. Weighting vectors of the harmonic components are adaptively updated based on a modified filtered-x least mean square (MFxLMS) algorithm, which has both strong robustness and much less computational complexity. The convergence properties of the proposed MFxLMS algorithm are investigated, and it is further implemented in a real-time controller. Experimental results on a standard vibrator show excellent performances for harmonic cancellation. The harmonic distortion is close to 0% after the implementation of the proposed algorithm.